(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article is devoted to the features of conducting an audit of financial statements prepared in accordance with international standards in Uzbekistan, in which the relevance of studying this topic, the level of study, the features of organizing an audit of financial statements prepared in accordance with international standards, the opportunities achieved in the implementation of IFRS and AAS in practice, issues to be studied in the process of auditing transactions made after the date of preparation of financial statements, the differences in the audit of financial statements prepared using parallel accounting (conversion) and transformation methods, and practical recommendations for improving this process are formulated.